CALL in EFL Classroom: How is lecturers’ perceptions in implementation? - Widyani Solihat (Universitas Muhammadiyah Semarang, 2018)
Computer Assisted Language Learning (CALL) is the implementation in the area of computer’s application or software as a technology which is used in teaching and learning of second language context. Nowadays, most universities are implementing the new technologies in their classes: such as computers, tablets, interactive whiteboards, LCD or even mobile phones to support the learning process. Utilizing technologies in education area has been increased because of the globalization process. Some universities do not utilize technology well to assist language learning process. The possible solution to solve the problem is introducing a knowledge about CALL. The aim of this study is to know the lecturers’ perception about CALL. This study used the qualitative method with individual interview technique. There were three EFL lecturers who served as the sample of this research. Two steps were done to gain lecturers’ perception toward CALL: (1) introduced CALL to the lecturers and tried to implement it during language learning process; (2) interviewed the lecturers to gain their perceptions toward CALL. The findings of this study show that CALL helps the lecturer to support their language learning process. The lecturers declared that CALL is very useful in language learning process.